'Slow and Steady can Still Win the Race': Childhood Vaccination Experience of Migrant Ebira Women Within the Health System in Ekiti State, Nigeria - Olakanmi-Falade Bukola (Light House Polyclinic Mangalore, 2021)
Background: Nigeria is yet to attain universal vaccination coverage for its children below two years of age. Although efforts are being made to identify all the possible determinants, the contributions of the migrant communities are yet to be fully explored. Methods: A mixed-methods approach was adopted. Results: The respondents were highly aware of childhood immunization. Peculiar to this migrant population, utilization of immunization was more likely in women in the lowest wealth quartile. Other factors associated with completion of immunization included having a spouse who supported immunization, having a good knowledge of the timing and description of the doses given at birth, having given birth in a medical facility and possession of a child-vaccination card. Conclusion: 'Slow and steady steps' that could increase coverage including promoting hospital deliveries, scaling up dissemination of information on immunization in the local dialect, advocacy through religious leaders and community-based initiatives are recommended.